Antidiabetic Properties and Toxicological Assessment of Antidesma celebicum Miq: Ethanolic Leaves Extract in Sprague–Dawley Rats - Raysa Y. Pratiwi; Berna Elya; Heri Setiawan; Roshamur C. Forestrania; Rizna T. Dewi (Advances in Pharmacological and Pharmaceutical Sciences)
Antidesma is a genus of plants, and its several species are known to have antidiabetic properties. Leaves of Kayu Tuah (Antidesma celebicum Miq) have been proven to have the best α-glucosidase inhibition ability compared to other species in the Antidesma genus, as evidenced by the in vitro α-glucosidase inhibition test. However, no scientific studies have reported its antidiabetic properties and toxicity in vivo. Therefore, this research managed to verify the antidiabetic features and safety of ethanolic extract of A. celebicum leaves (EEAC) in Sprague–Dawley rats. Male rats (170–280 g) were induced diabetic with streptozotocin (35 mg/kg BW) and fed a high-fat diet comprising 24% fat, whereas control group rats were given a standard diet. Rats were treated with EEAC at 200 and 400 mg/kg BW doses for 28-days and 60 mg/kg BW acarbose for the control group. Determination of antidiabetic properties was done by analyzing lipid profiles as well as fasting blood glucose. After confirming the antidiabetic properties of EEAC, the toxicological assessment was determined using the fixed-dose method. General behavior changes, appearance, signs of toxicity, mortality, and body weight of animals were marked down during the observation period. When the treatment period ended, hematological, biochemical, and histological examinations of liver, kidneys, and heart sections were performed. The results confirmed that EEAC reduced fasting blood glucose levels and stepped forward lipid profiles of rats. Also, all animals survived, and no obvious destructive outcomes were noticeable during the study. As EEAC has promising results toward hyperglycemia and hyperlipidemia and has been proven safe through toxicity tests, it can be concluded that EEAC has good potential to be further developed into antidiabetic drugs.